2019
DOI: 10.1093/jxb/ery465
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling new molecular players involved in the autoregulation of nodulation inMedicago truncatula

Abstract: We provide new insights into the autoregulation of nodulation that allow us to better understand how the legume Medicago truncatula restricts further nodulation once enough nodules have been formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 67 publications
2
52
0
Order By: Relevance
“…As a proof of concept, we first described in M. truncatula the detection of epistatic selection between the Super Numeric Nodule MtSUNN gene, encoding a receptor which is central for the negative regulation of symbiotic root nodulation, and the CLAVATA3-like (CLE) signaling peptide MtCLE02 . This finding is reminiscent of the functional interaction proposed for other CLE signalling peptides, MtCLE12 and MtCLE13 previously shown to require the MtSUNN receptor to regulate negatively the number of nodule organs on the plant root system (29, 30). Accordingly, an ectopic expression of the MtCLE02 gene in M. truncatula wild-type and sunn mutant roots experimentally demonstrated a MtSUNN -dependent negative role of the MtCLE02 gene on nodulation, hence validating functionally the genetic interaction between these two genes.…”
Section: Introductionsupporting
confidence: 63%
“…As a proof of concept, we first described in M. truncatula the detection of epistatic selection between the Super Numeric Nodule MtSUNN gene, encoding a receptor which is central for the negative regulation of symbiotic root nodulation, and the CLAVATA3-like (CLE) signaling peptide MtCLE02 . This finding is reminiscent of the functional interaction proposed for other CLE signalling peptides, MtCLE12 and MtCLE13 previously shown to require the MtSUNN receptor to regulate negatively the number of nodule organs on the plant root system (29, 30). Accordingly, an ectopic expression of the MtCLE02 gene in M. truncatula wild-type and sunn mutant roots experimentally demonstrated a MtSUNN -dependent negative role of the MtCLE02 gene on nodulation, hence validating functionally the genetic interaction between these two genes.…”
Section: Introductionsupporting
confidence: 63%
“…In addition to the common symbiotic pathway essential for early signaling and infection events in nodulation and AM (Radhakrishnan et al, 2020), we might consider this negative regulation of symbioses via autoregulation as the bookend to this pathway and therefore a component of the so called 'common symbiotic pathway' (Chiu and Paszkowski, 2020). Indeed, recent studies have suggested AON may influence a subset of genes, including the Nod-factor receptor NFP (Gautrat et al, 2019), integrating these two programs. It is also interesting to consider that although the CLV-CLE pathway shares an orthologous role in shoot apical meristem control in non-legumes, no clear role for CLV1-like genes in shoot development of legumes has been observed (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Key downstream root acting players include the kelch repeat-containing F-box protein TML (Gautrat et al, 2019;Magori et al, 2009;Takahara et al, 2013), and the transcriptional regulation of nod factor receptors (Gautrat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…TOO MUCH LOVE (TML), the target of miR2111, restricts nodule formation [127]. However, in the absence of rhizobia, miR2111 is expressed in leaf CCs and translocates to the roots, where mature miR2111 post-transcriptionally regulates TML, which down-regulates genes that affect nodulation factor perception and thus inhibits repression of nodulation [182]. Following exposure to rhizobia, a CK-dependent signal from roots inhibits miR2111 production in the shoot, which allows TML to limit nodule formation [127,128].…”
Section: Nodulationmentioning
confidence: 99%